Structural elements that modulate the substrate specificity of plant purple acid phosphatases Avenues for improved phosphorus acquisition in crops - Feder, Daniel (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2020 Elsevier B.V. All rights reserved.